Informing medical students about the effects of climate change on health - AGACHIE, Lia-Mirela (One Health & Risk Management, 2021)
Introduction. The phenomenon of climate change increases the risk of health problems, having direct and indirect effects. Physicians of all specialties, through their role as promoters and educators in the field of health, are reliable sources of information. Thus, medical education must undergo transformations, an era in which medical universities are the basic link attributed to raising awareness of the role of health workers in the process of preventing the undesirable effects of climate change and adapting to new living conditions must begin. A medical curriculum on climate change has the greatest potential to reach large cohorts of professionals and allow for standardization between institutions.The aim of the study was to establish the need for medical students in information, additional knowledge about the problems of climate change, global warming, heatwaves, heat stress, their health consequences and prevention measures.Material and methods. A described study was designed applying the sociological method, using an elaborate questionnaire. The study involved 101 medical students. In order to elaborate the questionnaire and study the topicality of the problem, 18 bibliographic sources selected in PubMed were analyzed.Results. By conducting this study, we were asked whether medical students need more information about the problems of climate change, global warming, heatwaves, heat stress, their health consequences, prevention measures and correct behavior.About 2/3 (66 people) of respondents stated the need to supplement knowledge on the influence of global warming on human health in professional activity. Of the 66 respondents, only 46 agreed to answer the open-ended question about what they would actually be interested in knowing. Respondents' responses practically cover all information related to global warming (starting with the factors, causes of global warming) and health (influence, prevention measures, adaptation). Most of the answers were concrete, but there were also answers like: "Everything about global warming", "As much as possible", "Everything related to the heat".Among the respondents who were interested in the issues of global warming, requests for additional information referred to: "Risks caused by global warming on the environment and the human body, on different age groups, on patients with various diseases", "Negative impact of global warming on human health","Consequences of global warming (evidence-based; direct and indirect) on the body","Evolution and dynamics of diseases depending on changes in the environment", Results of clinical trials" other respondents specifically stated that they are interested in the impact on the cardiovascular, respiratory system.Most respondents are also interested in "Measures, methods to prevent the adverse effects of global warming on human health", "Mechanisms and projects that are implemented to reduce environmental pollution", "Protective measures for people with chronic diseases", "How it is recommended to be the diet, because fruits and vegetables also suffer from overheating "," How to protect ourselves and prevent the consequences of global warming on human health ".Conclusions. Both the general answers of the respondents and the lack of answer to the open-ended question confirm the need to raise awareness of the problem and increase the level of knowledge.